Experience of nursing students in peripheral venous puncture technique with and without the use of portable skin transillumillator (Research, Society and Development, 2021)
Objective: To describe the experience of nursing students in the technique of peripheral venous puncture with and without the use of portable cutaneous transillator. Method: Observational, descriptive, cross-sectional and quantitative study conducted in a private college in the city of Curitiba-Paraná. Participants were 18 students randomly divided into two groups:  Group I (traditional technique, without the use of portable skin transilluminator - venoscope) and Group II (technique with the use of venoscope). Data were collected using two instruments developed by the researchers containing demographic variables and questions related to venoscope use. Descriptive and inferential statistics were used for data analysis. Results: There was a significant correlation between the theoretical knowledge of venous puncture and the identification of the vessel to be punctured (p=0.000), and the theoretical knowledge with the level of difficulty to puncture (p=0.005).  Regarding the number of puncture attempts,33.3% of the students successfully punctured the first attempt with the venoscope, for 44.4% of the students without the use of the device. When addressing the experience with the use of the venoscope, 66.7% mentioned being advantageous, and 55.6% reported that its use favored the visualization of veins. Conclusion: Venous puncture with the use of the venoscope was valid for learning and considered an advantageous experience for the students.